UNDERSTANDING TABOOS: A WINDOW INTO CULTURE AND SOCIETY - Nigora Yusupova; Melihol Xushboqova; Surayyo Xursandova (TADQIQOTLAR, 2025)
This  article  explores  the  concept  of  taboos  across  cultures,  examining  their origins, types, and societal roles. It highlights how taboos function as a reflection of cultural values and norms, while also noting how modern perspectives are reshaping some traditional beliefs. By investigating various examples and considering current shifts,  we  aim  to  offer  a  deeper  understanding  of  how  taboos  impact  individual behavior and collective society.